Advances in pharmacotherapy for acute kidney injury. (13th April 2022) - Xu, Yali; Zou, Ping; Cao, Xiaojing
ABSTRACT: Introduction: Acute kidney injury (AKI) is a clinically critical disease exhibiting an acute decline in renal function. The lack of an effective prevention and treatment method equates to a high morbidity and mortality rate. Consequently, over the past few decades, many therapeutic drugs with different mechanisms of action have been proposed and gradually applied to the clinic. The involved drug mechanisms evaluated have included hemodynamic modulation, anti-inflammatory, antioxidant, repair agents, metabolic derangement and mitochondrial function. Areas Covered: The authors of this review provide the reader with a reference point for the latest advances in pharmacotherapy in acute kidney injury. This is achieved by the evaluation of the latest data collected on potential therapeutic drugs with different mechanisms of action, as well as their preclinical and clinical impact on AKI. Expert opinion: Presently, the vast majority of drugs are still in clinical development, which is a huge challenge. Nevertheless, in addition to current chemical drugs and gene therapy strategies, the advent of mesenchymal stem cell treatments and other emerging pharmaceutical strategies could enable clinicians to better treat AKI. Due to the nonselective distribution and low bioavailability of some of the latest pharmaceutical strategies, there is hope that these treatment options may provide more efficacious avenues.